Characterization of Pinus spp. needles by gas chromatography and mass spectrometry: Application to plant-insect interactions - Mateus, E. (2011)
Dissertação apresentada para obtenção do Grau de Doutor em Ciências do Ambiente pela Universidade Nova de Lisboa, Faculdade de Ciências e Tecn